EFFECTS OF SINGLE FAMILY ROOM ARCHITECTURE ON PARENT– INFANT CLOSENESS AND FAMILY CENTERED CARE IN NEONATAL ENVIRONMENTS : A single center pre–post study - Hongisto, Pilvi (My University, 2021)
The aim of the study was to evaluate the effects of a neonatal intensive care unit (NICU) moving from a unit with shared patient rooms into a unit with single family rooms (SFRs) on the duration of parent ́s presence and skin to skin contact (SSC) and on the parents’ experiences of the quality of family centered care (FCC). In this pretest-posttest study, the parents of preterm infants were asked to report in daily diaries the time a) in the NICU and b) of SSC with their infant and to evaluate the quality of FCC in two different time points in contrasting NICU environments. The duration of time the parents were present in the NICU increased significantly in the SFR unit but was not reflected in the amount of SSC. In their evaluations of the quality of FCC, the parents offered highly positive experiences, regardless of the unit architecture and no significant differences occurred neither at the total evaluations nor at single question level. In conclusion, the unit architecture increased the parents’ presence in a NICU but not SSC. Being more in the unit with SRFs did not affect the parents' evaluations of the quality of FCC.
Keywords: single-family room, family centered care, NICU, perhehuone, perhekeskeinen hoito, vastasyntyneiden teho-osasto